i-seeuWatch / Nur Shafinah Mahrul … [et al.] - Mahrul, Nur Shafinah; Rusdi, Nadhilatul Zhafirah; Idimin, Frederisca Gloria; Sun Fatt, Boyd (Faculty of Computer and Mathematical Sciences, 2022)
The 24 hours of a visually impaired person's life are a hard test that no parable can completely convey; life for them is extremely different from life for someone with great eyes. The mobility of the blind is restricted. According to the World Health Organization, there are currently more than 285 million visually impaired people living in the world. Of those, only 50,000 or so are officially registered with the Malaysian Welfare Department, and an additional 50,000 are presumed to be living without identification for a variety of reasons. One of the products that can help people with vision impairment is the i-seeuWatch (blind). The i-primary seeuWatch's purpose is to aid blind people and individuals with severe vision impairments by providing a complete location and a sophisticated system that allows them to just speak, and the watch will direct them; all they have to do is follow the instructions given by the watch system. When they ask a question, the watch leaves a voice message. Additionally, by offering early warning, the distinctiveness of this i-seeuWatch can help and facilitate OKU (blind) users. The areas are explored using sound sensors, and they also give users a vibration they may feel on their arms. Next, this watch have provided complete GPS access on this watch, which will work automatically for 24 hours non-stop to track their whereabouts. The i-seeuWatch will send real-time notifications to users without requiring them to open the app. The goal of developing this product is to make it easier to use for blind users. This rubber product is lighter and more flexible. It is also washable and resistant to sand, seawater, and moisture. This product uses purple and yellow colors. The color yellow evokes a cheerful spirit, joy, and relaxation, while the color purple can provide serenity and inspiration. Magnets are also included to allow users to adjust the size of the bracelet according to their comfort